Utilização de um núcleo energético-protéico como melhorador do desempenho produtivo e características de carcaça de frangos de corte. - Dallmann, Henrique Müller (2010)
This study aimed to investigate the effect of an energetic-protein nucleus (EPN) fed from hatch to 21 days-old broiler chicks. The nucleus was composed by degummed soybean oil, pre-gelatinized corn, bi-processed soybean, mannanoligosaccharide and peptides. A total of 864 day-old male AGRoss broiler chicks were allocated in 32 pens (27 birds per pen and 8 replicates per treatment). Treatments consisted of T1 Control (0% EPN), T2 7% EPN (1-7 days) and 3,5% EPN (8-21 days), T3 14% EPN (1-7 days) and 7% EPN (8-21 days) and T4 21% EPN (1-7 days) and 10,5% EPN (8-21 days of age). The diets were fed from hatch up to 21 days of age. From 21 to 42 days of age, birds were fed a unique basal diet. Body weight, weight gain, feed intake, feed conversion and carcass yield and cut-ups were evaluated. Results indicated the the EPN had not influenced performance, carcass traits and cut-ups of broilers when fed up to 21 days of age.